1973
DOI: 10.1001/archinte.1973.00320090067007
|View full text |Cite
|
Sign up to set email alerts
|

Single-Agent Therapy for Hodgkin's Disease

Abstract: We have reviewed existing data on single drugs in the chemotherapy of Hodgkin's disease in order to place in perspective the recent results with regimens employing combinations of drugs. Combination chemotherapy, by historical comparison with single-drug therapy, is clearly superior in the induction of complete remission of disease. However, many single agents, particularly those in the antimetabolite and antibiotic classes of antitumor drugs, have been evaluated only minimally and may yet play important roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Of course it was our concern that an already occult malignancy had been further masked by partial treatment. However, it is unlikely that these drugs singly or together in the doses used were adequate to induce remission of Hodgkin's disease (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Of course it was our concern that an already occult malignancy had been further masked by partial treatment. However, it is unlikely that these drugs singly or together in the doses used were adequate to induce remission of Hodgkin's disease (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Vinblastine, a vinca alkaloid, is a highly effective agent for patients with HD. Early studies have shown a response rate of 90% and a cure rate of 10% when it is used as singleagent front-line therapy [54]. It has also been studied in the relapsed setting at the National Cancer Institute in 17 patients who experienced treatment failure with autologous transplantation [55].…”
Section: Single-agent Therapymentioning
confidence: 99%